2012
DOI: 10.1017/s1368980011003624
|View full text |Cite
|
Sign up to set email alerts
|

The cost associated with disease-related malnutrition in Ireland

Abstract: Objective: The present study aimed to establish the annual public expenditure arising from the health and social care of patients with diet-related malnutrition (DRM) in the Republic of Ireland. Design: Costs were calculated by (i) estimating the prevalence of DRM in health-care settings derived from age-standardised comparisons between available Irish data and large-scale UK surveys and (ii) applying relevant costs from official sources to estimates of health-care utilisation by adults with DRM. No attempt ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 27 publications
(38 reference statements)
0
22
0
1
Order By: Relevance
“…Except one study conducted in a Gastroenterology Ward [7] all the others were multidisciplinary [6,7,10,13,15,18,23e25]. For nutritional status, one study used the NRI [15], one the SGA [7], four the NRS-2002 [6,13,18,24], two the Malnutrition Universal Screening Tool (MUST) [23,25] and one used Body Mass Index (BMI) and weight loss [10]. Most malnutrition rates ranged from 19 [7] to 44% [10], with the exception of the Croatian study, which reported a much lower prevalence (3.37%) [24].…”
Section: Impact Of Malnutrition On Hospital Costsmentioning
confidence: 99%
See 2 more Smart Citations
“…Except one study conducted in a Gastroenterology Ward [7] all the others were multidisciplinary [6,7,10,13,15,18,23e25]. For nutritional status, one study used the NRI [15], one the SGA [7], four the NRS-2002 [6,13,18,24], two the Malnutrition Universal Screening Tool (MUST) [23,25] and one used Body Mass Index (BMI) and weight loss [10]. Most malnutrition rates ranged from 19 [7] to 44% [10], with the exception of the Croatian study, which reported a much lower prevalence (3.37%) [24].…”
Section: Impact Of Malnutrition On Hospital Costsmentioning
confidence: 99%
“…Most selected studies reported additional costs, defined as the extra cost involved in treating all malnourished patients in the general population compared to treating the same number of wellnourished individuals [6,7,10,13,18,23,25]. Five studies reported overall costs [10,15,23e25], and four studies reported detailed costs (hospital, diagnosis, therapies and medications costs) [6,7,13,15,18].…”
Section: Impact Of Malnutrition On Hospital Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…Las más reconocidas son la Valoración Global Subjetiva (SGA, por su nombre en inglés) y la Evaluación Mini Nutricional (MNA) 8,11,12 ; no obstante, su aplicación toma un tiempo apreciable 13,14 . Otras son de más fácil aplicación: a destacar, la MNS-SF (Mini Nutritional Assesment-short form) es una herramienta validada que consta de 6 ítems, sin embargo, incluye una medida antropométrica (el índice de masa corporal) o en su defecto la circunferencia de la pantorrilla (MNA-SF modificada), para lo cual se requiere de personal entrenado e instrumentos.…”
unclassified
“…
Malnutrition is common in older adults, and is associated with high healthcare costs and adverse outcomes, particularly in hospital settings (1,2) . The prevalence and correlates of malnutrition in hospitalised older adults are currently not clear; much of the existing research in this area is limited methodologically; studies are typically based on small samples and/or narrow populations (3,4) , exclude people with dementia (3,4) , are uni-centre (5) , and/or use tools not designed for use with older adults (5) .
…”
mentioning
confidence: 99%